The effects of magnetic casson blood flow in an inclined multi-stenosed artery by using caputo-fabrizio fractional derivatives - Jamil, Dzuliana Fatin; Uddin, Salah; Kamardan, Muhamad Ghazali; Roslan, Rozaini (Penerbit Akademia Baru, 2021)
Hemodynamic is the knowledge of blood circulation, which is useful in the diagnosis of coronary illness. The reason behind the malfunction of cardiovascular system is the presence of fats, cholesterol and lipoproteins at the sites of atherosclerotic lesion in the artery [1]. In recent years, due to its great importance in the human cardiovascular system, the study of blood flow through constricted arteries has received a great deal of attention [2–4]. Prasad and Radhakrishnamacharya [5] considered the steady blood flow through an inclined non-uniform tube with multiple stenoses. Agarwal and Varshney [6] studied the flow of Herschel-Bulkley fluid through an inclined tube of nonuniform cross-section with multiple stenoses. Biswas and Paul [7] observed the steady blood flow through an inclined tapered vessel, where the blood was modelled as Newtonian fluid and the slip vessel wall condition was applied. Also, their analysis includes one-dimensional Poiseuille blood flow through tapered vessels with inclined geometries. Ismail and Jamali [8] explored the dynamic response of heat transfer in the steady laminar blood flow through the stenotic bifurcated artery.